Multidrug resistant commensal Escherichia coli in animals and its impact for public health - Szmolka, Ama; Nagy, Béla (Frontiers in Microbiology, 2013)
After the era of plentiful antibiotics we are alarmed by the increasing number of antibiotic resistant strains. The genetic flexibility and adaptability of Escherichia coli to constantly changing environments allows to acquire a great number of antimicrobial resistance mechanisms. Commensal strains of E. coli as versatile residents of the lower intestine are also repeatedly challenged by antimicrobial pressures during the lifetime of their host. As a consequence, commensal strains acquire the respective resistance genes, and/or develop resistant mutants in order to survive and maintain microbial homeostasis in the lower intestinal tract. Thus, commensal E. coli strains are regarded as indicators of antimicrobial load on their hosts. This chapter provides a short historic background of the appearance and presumed origin and transfer of antimicrobial resistance genes in commensal intestinal E. coli of animals with comparative information on their pathogenic counterparts. The dynamics, development, and ways of evolution of resistance in the E. coli populations differ according to hosts, resistance mechanisms, and antimicrobial classes used. The most frequent tools of E. coli against a variety of antimicrobials are the efflux pumps and mobile resistance mechanisms carried by plasmids and/or other transferable elements. The emergence of hybrid plasmids (both resistance and virulence) among E. coli is of further concern. Co-existence and co-transfer of these “bad genes” in this huge and most versatile in vivo compartment may represent an increased public health risk in the future. Significance of multidrug resistant (MDR) commensal E. coli seem to be highest in the food animal industry, acting as reservoir for intra- and interspecific exchange and a source for spread of MDR determinants through contaminated food to humans. Thus, public health potential of MDR commensal E. coli of food animals can be a concern and needs monitoring and more molecular analysis in the future.